PENGARUH RISIKO BISNIS, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pratama, Riski Putra; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to examine the persial and simultaneous influence of business risk, firm size and sales growth on capital structure. Where independent variable in this research is business risk, firm size and sales growth while dependent variable is capital structure. The sample used is secondary data derived from the financial statements of real estate and property companies listed on the Indonesia Stock Exchange (IDX) period 2011 to 2015. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis. The results of this study indicate that the variable of business risk, firm size and sales growth in persial (t test) does not affect the capital structure in the real estate and property companies listed on the Indonesia Stock Exchange. The simultaneous test results (F) show that there is no effect of business risk, firm size and sales growth on capital structure on real estate and property companies listed in Indonesia Stock Exchange.Keywords: business risk, firm size, sales growth and capital structure